Phylogeography and population genetics of a widespread cold‐adapted ant, Prenolepis imparis. Issue 18 (3rd August 2022) - Tonione, Maria Adelena; Bi, Ke; Dunn, Robert R.; Lucky, Andrea; Portik, Daniel M.; Tsutsui, Neil Durie
Abstract: As species arise, evolve and diverge, they are shaped by forces that unfold across short and long timescales and at both local and vast geographical scales. It is rare, however, to be able document this history across broad sweeps of time and space in a single species. Here, we report the results of a continental‐scale phylogenomic analysis across the entire range of a widespread species. We analysed sequences of 1402 orthologous ultraconserved element (UCE) loci from 75 individuals to identify population genetic structure and historical demographic patterns across the continent‐wide range of a cold‐adapted ant, the winter ant, Prenolepis imparis . We recovered five well‐supported, genetically isolated clades representing lineages that diverged from 8.2–2.2 million years ago. These include: (i) an early diverging lineage located in Florida, (ii) a lineage that spans the southern United States, (iii) populations that extend across the midwestern and northeastern United States, (iv) populations from the western United States and (v) populations in southwestern Arizona and Mexico. Population genetic analyses revealed little or no gene flow among these lineages, but patterns consistent with more recent gene flow among populations within lineages, and localized structure with migration in the western United States. High support for five major geographical lineages and lack of evidence of contemporary gene flow indicate in situ diversification across the species' range, producing relatively ancient lineages that persisted through subsequent climate change and glaciation during the Quaternary.